Tinjauan Pengaturan Waktu Sinyal pada Persimpangan Empat Lengan Menggunakan Pendekatan Manual Kapasitas Jalan Indonesia dan Webster - Rani Bastari Alkam; Suriati Abd. Muin; Istiawan Istiawan; Dzal J.W.Ikram Syam (Departemen Teknik Infrastruktur Sipil Institut Teknologi Sepuluh Nopember Surabaya, 2021)
Signal timing according to actual traffic is pivotal for optimizing the intersection performance. This study aims to compare the performance of Adiyaksa-Pengayoman intersection using the MKJI and Webster and to review the compatibility between the existing signal timing and research results. The traffic survey was carried out for three days on Wednesday, Friday and Sunday from 07.00-17.00. Data were analyzed using MKJI and webster analysis procedures. The results showed that for the MKJI, the degree of saturation of the East, South, and West approaches was greater than 0.7 while the western was less than 0.6. Meanwhile for the webster, the saturation degree of East, South, and North was greater than 0.5 while for the western approach is less than 0.3 except on Wednesday afternoon with 0.539. Fixed signal timing at intersections is contradictory to the results which shows the cycle time fluctuates according to traffic volume at each observation time.